The autobiographical turn in germanophone documentary and experimental film - Curtis, Robin, 1964-; Fenner, Angelica (Rochester, New York : Camden House, 2014)
A volume of essays marking out a new, historically and culturally specific model for contemplating autobiographical non-fiction film and video. There is a widespread notion in the scholarly literature on autobiographical nonfiction film that there are unchanging, universal models for the investigation of the self through audiovisual media. By insisting on the cultural andhistorical specificity of that self, the essays in this volume trace the range of politically and theoretically informed taboos, critiques, and proclivities that shape autobiographical filmmaking in German-speaking countries. Indoing so, they delineate a new model for contemplating autobiographical film and video. The essays in this volume examine the parameters shaping the audiovisual self in the Germanophone cultural context across a variety of practices and aesthetic modes, from contemporary artists including Hito Steyerl, Ming Wong, and kate hers to Rolf Dieter Brinkmann's multimedia experiments of the 1970s, and from Helke Misselwitz's challenges to the documentary tradition in the GDR to Peter Liechti's investigations of Swiss ambivalence toward the nation's iconic landscape. The volume thus takes up a number of historically and geographically specific iterations of autobiographical discourse that in each case remain contingent on the space and time in which they are uttered. Contributors: Dagmar Brunow, Steve Choe, Robin Curtis, Tobias Ebbrecht-Hartmann, Angelica Fenner, Marcy Goldberg, Feng-Mei Heberer, Rembert Hüser, Waltraud Maierhofer, Christopher Pavsek, Patrik Sjöberg, Carrie Smith-Prei, Anna Stainton. Robin Curtis is Professor of Theory and Practice of Audiovisual Media at the Heinrich-Heine-University in Düsseldorf, Germany. Angelica Fenner is Associate Professor of German and Cinema Studies at the University of Toronto.
""Part IV. Revisiting Authorship in New German Cinema""""10: Reauthoring the Self: Brinkmanns Zorn""; ""11: From Death to Life: Wim Wenders, Autobiography, and the Natural History of Cinema""; ""12: â€œIch binâ€?s, Fassbinder, â€? or The Timing of the Self""; ""Filmography""; ""Bibliography""; ""Notes on the Contributors""; ""Index""
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Biographical films -- Germany -- History and criticism; Documentary films -- Germany -- History and criticism; Self in motion pictures; Moi (Psychologie) au cinéma.; Films biographiques -- Allemagne -- Histoire et critique; Documentaires -- Allemagne -- Histoire et critique; PERFORMING ARTS -- Reference; Biographical films; Documentary films; Self in motion pictures; Germany; German-speaking countries; Helke Misselwitz; Hito Steyerl; Ming Wong; Peter Liechti; Rolf Dieter Brinkmann; audiovisual media; autobiographical discourse; autobiographical non-fiction film; kate hers; space and time; Criticism, interpretation, etc